Bronchial asthma and chronic obstructive pulmonary disease: diagnostic capabilities in a doctor’s practice - A. I. Mikhaylovicheva; V. V. Smirnov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The article discusses the possibilities of functional diagnostics of the respiratory function of the lungs in patients with bronchial asthma and chronic obstructive pulmonary disease. Functional diagnostic methods such as capnometry, spirometry, assessment of lung diffusivity and multiple breath nitrogen washout can be used not only to assess airway dysfunction, but also to monitor the course of the disease. There is a need for further development of methods for studying the respiratory function of the lungs and, if possible, their introduction into everyday clinical practice. The purpose of this review was the possibility of diagnostic tests to assess the ventilation and gas exchange function of the lungs in patients with bronchial asthma and chronic obstructive pulmonary disease.